Characterization of human chromosomal DNA sequences which replicate autonomously in Saccharomyces cerevisiae. - Montiel, J; Norbury, C; Tuite, M; Dobson, M; Mills, J; Kingsman, A; Kingsman, S (1984)
We have characterised two restriction fragments, isolated from a "shotgun" collection of human DNA, which function as autonomously replicating sequences (ARSs) in Saccharomyces cerevisiae. Functional domains of these fragments have been defined by subcloning and exonuclease (BAL 31) deletion analysis. Both fragments contain two spatially distinct domains. One is essential for high frequency transformation and is termed the Replication Sequence (RS) domain, the other, termed the Replication Enhancer (RE) domain, has no inherent replication competence but is essential for ensuring maximum function of the RS domain. The nucleotide sequence of these domains reveals several conserved sequences one of which is strikingly similar to the yeast ARS consensus sequence.